Intrascleral Tunnel Clamping of Fluocinolone Acetonide Implant: A Novel Scleral Fixation Technique - Lucas Sejournet; Laurent Kodjikian; Thibaud Mathis; Alban Comet; Pierre Gascon; Frederic Matonti (Pharmaceuticals)
Purpose: This retrospective observational study evaluates the efficacy and safety of a novel scleral fixation technique of the fluocinolone acetonide (FAc) implant in four consecutive patients with post-surgical macular edema (PSME). Case Presentation: Four patients with PSME underwent intrascleral tunnel clamping (ITC) of the FAc implant due to lens defects. A 25-gauge sclerotomy was made 3.5 mm from the limbus and the implant was inserted into it until its end reached the edge of the sclera. Then, an 8-0 absorbable suture was passed through the sclera without penetrating the implant, thereby clamping the sclera around the FAc. All the patients showed improvements in best-corrected visual acuity (from a mean of 20/100 at baseline to 20/40) and central retinal thickness (from a mean of 534 µm at baseline to 318 µm) and with no recurrence of macular edema in most cases, without the need for further treatment. In addition, no anterior migration of the FAc implant or ocular hypertension was observed. This procedure effectively reduced the therapeutic burden for these patients. Although scleral fixation of the FAc implant has been described in small series of patients with successful results, this approach remains off-label. Conclusions: Although off-label, ITC of the FAc implant may offer a promising treatment option for patients who would otherwise remain untreated.